Ethical Problems in New Religion Field Research - Dallam, Marie W. (Religion compass, 2011)
Scholars studying living religious communities confront myriad questions about all levels of appropriate social interaction, and fortunately some lessons from the disciplines of sociology and anthropology help us navigate the work. However, those engaging in research on New Religions may have added burdens, as the marginalized communities we study may be further complicated by factors such as exclusivity or defensiveness, among others. As we work to balance critical academic study with engagement that is sensitive to practitioners, we may find ourselves in murky ethical situations. This essay, the second of a two-part series, discusses a range of unique ethical problems that those researching New Religions may confront, and for possible guidance it refers to specific examples faced by scholars in the past.